Outcomes in patients undergoing percutaneous ventricular assist device implantation for cardiogenic shock. Issue 2 (April 2016) - Berg, David D; Sukul, Devraj; O'Brien, Molly; Scirica, Benjamin M; Sobieszczyk, Piotr S; Olenchock, Benjamin A; Bohula, Erin A; Morrow, David A
Background: Percutaneous ventricular assist devices (PVADs) offer an important but resource-intensive option for management of severe cardiogenic shock (CS). Optimal selection of patients for PVAD support remains undefined. We investigated outcomes, including characteristics associated with in-hospital survival, during PVAD support for CS. Methods: We established a prospective quality improvement program among patients undergoing TandemHeart PVAD implantation for CS at Brigham and Women's Hospital (Boston, MA). We evaluated 65 consecutive patients between 2006 and 2014, analyzing demographic, clinical, laboratory, hemodynamic, and survival data. Results: Thirty-two patients (49.2%) survived to hospital discharge, of which 12 received destination surgical therapy. Baseline characteristics associated with survival included younger age (47 ± 15 years vs 61 ± 11 years; p <0.001), non-ischemic cardiomyopathy (NICMP) vs ischemic CMP (survival 70.4% vs 34.2%, p =0.004), and, paradoxically, lower presenting left ventricular ejection fraction (LVEF) (survival 66.7% for LVEF ⩽15%, 41.2% for LVEF 16–25%, 25.0% for LVEF >25%; p =0.010). Younger age ( p =0.026) and NICMP ( p =0.034) remained independent predictors of survival. Twenty-four hours after PVAD placement, a more modest increase in cardiac index (⩽0.75 L/min/m 2 ) was associated with higher in-hospital mortality (OR 6.3, 95% CI 1.8–22.1), as was lack of improvement in serum anion gap (⩽2 mEq/L; OR 5.1, 95% CI 1.6–16.6). Conclusions: Despite intensive care and provision of circulatory support, survival is poor in severe CS. Patients in CS with younger age and NICMP were more likely to survive to hospital discharge. Less robust hemodynamic improvement and persistent acidosis after 24 hours of PVAD support also identified patients less likely to survive.